1997
DOI: 10.1111/j.1600-0420.1997.tb00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical results of responders and non‐responders to the prism adaptation test in intermittent exotropia

Abstract: ABSTRACT.The data for 94 consecutive patients with intermittent exotropia of basic type, ranging from 20 to 40 prism diopters (A), who preoperatively wore neutralizing prisms for 3 to 5 days, were studied retrospectively. The surgery in 43 patients in whom the amount of increase of angle was 4 A or less was based on the original angle (Group A), while that in 51 patients in whom the magnitude of increase was 5 A or more was based on the increased angle of deviation (Group B). Patients with initial deviation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…4,6,8 Thus, it prevents the risk of under-correction and also promotes the development of binocular sensory vision. 9,10 In our study, 13 of 18 patients (72.2 per cent) on whom PAT was conducted, showed an increment of five or more prism dioptres in the angle of deviation from six metres compared to the initial angle measured by prism. Consequently, surgical treatment for these patients consisted of larger muscle resection and recession.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…4,6,8 Thus, it prevents the risk of under-correction and also promotes the development of binocular sensory vision. 9,10 In our study, 13 of 18 patients (72.2 per cent) on whom PAT was conducted, showed an increment of five or more prism dioptres in the angle of deviation from six metres compared to the initial angle measured by prism. Consequently, surgical treatment for these patients consisted of larger muscle resection and recession.…”
Section: Discussionmentioning
confidence: 45%
“…Many studies indicate that preoperative prism correction allows a relatively accurate determination of the amount of the prism for surgery . Thus, it prevents the risk of under‐correction and also promotes the development of binocular sensory vision . In our study, 13 of 18 patients (72.2 per cent) on whom PAT was conducted, showed an increment of five or more prism dioptres in the angle of deviation from six metres compared to the initial angle measured by prism.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It has been suggested that the development of controlled force exertion ability is affected by acquired factors and that laterality becomes more marked over time [15]. Because the dominant hand is more frequently used in daily life and is more exposed to various stimulations, it was predicted that the dominant hand would perform better in matching demanded forces owing to their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Noguchi et al [6] reported that laterality is found in the Moving Beans with Tweezers test and the Purdue Pegboard test, which are used to evaluate dexterity, an element of coordination; their results indicated that the dominant hand is superior to the nondominant hand. Ohtsuki et al [7] found that laterality in grading ability becomes more pronounced with the influence of an acquired factor.…”
Section: Introductionmentioning
confidence: 99%